Resumption and its impact on the Grammatical Guidance for Qur’anic readings: An applied study on Surat Al-Baqarah (The International Journal for Scientific Research, 2023)
The study focuses on explaining the impact of resumption and its importance in the grammatical guidance of Qur’an readings in Surat Al-Baqarah. The importance of the study, on the one hand, stems from its connection with the Qur’an readings which is considered the main sources of citation on which linguists depend on when distilling Arabic grammar, and on the other hand, the study is connected with Surat Al-Baqarah in its applied aspect for its great merit and benefits, as it includes AyatulKursi, the greatest Ayah in the Qur’an.Resumption is a grammatical phenomenon that has its effective role in the grammatical guidance of Qur’an readings. The study aims to clarify the concept of grammatical resumption, knowing its tools and regulations, knowing the difference between grammatical resumption and rhetorical resumption, knowing the difference between the inceptive sentence, the resumed sentence, and pinpointing the function of the resumption letters, explaining their importance and impact on the inceptive sentence, and clarifying the impact of resumption on the vowel of parsing.Based on the descriptive analytical method, the most important results of the study are:Resumption affects the parsing position of the resumed word where the word that is judged to be the opening of the inceptive sentence exits from its previous motions to Damma, if it is in the accusative, or in the genitive, or in the jussive, it only exits to the nominative case rather than to the subjunctive as it was mentioned when the adjective is derived from the described.
Keywords: Resumption; the Vowel of Parsing; Guidance; Quran Reading